Home Purchase Decisions: An Analysis of Location, Promotion, and Price of Housing in Indonesia - Samudro, Amzad; Hamdan, Hamdan; Raharja, Indra (Dinasti Publisher, 2024)
This research is about purchasing decisions for Pantai Indah Kapuk 1 housing in Indonesia and this study aims to determine location, promotion and price analysis of housing purchase decisions at Pantai Indah Kapuk 1 and the respondents who are the owners of Pantai Indah Kapuk 1 housing. This research is descriptive quantitative. Primary data and secondary data obtained. Secondary data was obtained from various sources such as journalists, books and other related primary publication data obtained by distributing questionnaires to the target respondents. Determining the number of samples using purposive sampling technique and will be distributed via Google form to at least 150 respondents obtained. The results showed that location has a significant positive relationship with purchasing decisions, promotion has a significant positive relationship with purchasing decisions, and price has a significant positive relationship with purchasing decisions.